PENERAPAN METODE TOPSIS UNTUK EVALUASI KINERJA PENGAJAR - Dona, Dona; Husni, Rijalul (Riau Journal Of Computer Science, 2020)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that learners are actively developing their potential. . The relationship between education and teaching is very close. In this era, teachers are required to always do various improvements and adjustments in their professional abilities to face the challenges. Seeing the linkage between education and teachers, the evaluation process is absolutely necessary to improve the quality of the institution. With the evaluation, the policy makers can assess the gap between the standard set with the program carried out in the field to know the weakness of the program and the improvement of the program. In this study, the TOPSIS method will be used as the base model in the system to be created. TOPSIS is a method of Multiple Criteria Decision Making (MCDM) based on the measurement of distances between alternatives being considered and two alternate bipolar references, ideal positives and negatives. The goal to be achieved in this research is to provide ease and minimize policy-maker errors in the process of evaluating theÂ teacher